Saberes, práticas pedagógicas e concepções atuais dos professores de geografia na Rede Municipal de Imperatriz - SAMPAIO, Thiago da Silva (2021)
This dissertation-oriented study unfolds on the knowledge and pedagogical practices of teachers from the municipal education network of Imperatriz – MA. To better understand how this training takes place, we seek to understand the entire process from family culture, school education, academic training, disciplinary knowledge and knowledge and practices produced through experience in the exercise of teaching work. The research was conducted following a qualitative approach, which allowed us, through semi-structured interviews, to bring subjective responses, more spontaneous and more connected with the reality of the classroom. The interviews also allowed the teachers to go beyond the previously formulated questions, bringing valuable information about the daily life of their professional activity. Throughout the interview, we urged the professors about trends and theoretical-epistemological perspectives in geography, making them reflect on traditional, neo-geographical and critical theories. Teachers were also naturally urged to analyze the use of Traditional Geography (Conservative) and Critical Geography (Progressive) not only with regard to their work, but in their general perception of how this is configured in general terms in Geography. School of Basic Education. Nowadays, more than ever, actions that can promote connection and dialogue between basic schools and universities are needed, something that, in addition to being part of the composition of the theoretical body of this study, was questioned to teachers. It is important to establish a dialogue between professional professors and university professors so that both can together promote not only integration actions, but act together in the preparation of teaching materials and resources, in updating the curricular components and promoting practical activities in which these environments can coexist through teaching, research and extension. Considering that this study is part of a Professional Graduate Program, the research product consists precisely in the development of a didactic material entitled "School Geography of Southern Maranhão: Learning the contents in a local perspective", constructed as a result of the research and thinking about Geography teaching practices that are aligned with our regional and local realities, especially in southern Maranhão.